Haptoglobin therapy has differential effects depending on severity of canine septic shock and cell‐free hemoglobin level. Issue 12 (22nd October 2019) - Remy, Kenneth E.; Cortés‐Puch, Irene; Sun, Junfeng; Feng, Jing; Lertora, Juan J.; Risoleo, Thomas; Katz, Julia; Basu, Swati; Liu, Xiaohua; Perlegas, Andreas; Kim‐Shapiro, Daniel B.; Klein, Harvey G.; et al.
Abstract : BACKGROUND: During sepsis, higher plasma cell‐free hemoglobin (CFH) levels portend worse outcomes. In sepsis models, plasma proteins that bind CFH improve survival. In our canine antibiotic‐treated Staphylococcus aureus pneumonia model, with and without red blood cell (RBC) exchange transfusion, commercial human haptoglobin (Hp) concentrates bound and compartmentalized CFH intravascularly, increased CFH clearance, and lowered iron levels, improving shock, lung injury, and survival. We now investigate in our model how very high CFH levels and treatment time affect Hp's beneficial effects. MATERIALS AND METHODS: Two separate canine pneumonia sepsis Hp studies were undertaken: one with exchange transfusion of RBCs after prolonged storage to raise CFH to very high levels and another with rapidly lethal sepsis alone to shorten time to treat. All animals received continuous standard intensive care unit supportive care for 96 hours. RESULTS: Older RBCs markedly elevated plasma CFH levels and, when combined with Hp therapy, created supraphysiologic CFH‐Hp complexes that did not increase CFH or iron clearance or improve lung injury and survival. In a rapidly lethal bacterial challenge model without RBC transfusion, Hp binding did not increase clearance of complexes or iron or show benefits seen previously in the less lethal model. DISCUSSION: High‐level CFH‐Hp complexes may impair clearance mechanisms and eliminate Hp's beneficial effect during sepsis. Rapidly lethal sepsis narrows the therapeutic window for CFH and iron clearance, also decreasing Hp's beneficial effects. In designing clinical trials, dosing and kinetics may be critical factors if Hp infusion is used to treat sepsis.